Hailat Araka and the South Arabian Neolithic. (18th April 2013) - Zarins, Juris
Abstract : A small Neolithic lithic scatter site was discovered in 1992 through survey in the southern region of Dhofar, Oman just south of the Rub al Khali. Four test units (1994, 2009) confirmed a 60–90 cm single period Neolithic stratification sequence of the mid‐sixth millennium BC. Lithic debris contains all stages of knapping from prepared cores and is dominated by trihedral rod production. Based on comparable sites both to the west in Yemen and to the east in northern Oman/the UAE, it is suggested that still rare domesticated cattle and ovicaprids supplemented a basic forager lifestyle. Participation in long‐range trade networks involved marine shells, exotic flint tools as well as obsidian, steatite and amazonite. Genetic testing suggests that the Neolithic populations may represent ancestral Modern South Arabic Language (MSAL) populations currently living in southern Arabia.